Ações do ácido caurenóico e da l-arginina sobre o estresse oxidativo e a inflamação em retalhos cutâneos randomizados em ratos - Silva, Joaquim José de Lima (2015)
The protective effect of kaurenoic acid (KA) and of L-arginine (LA) on the oxidative stress and inflammation was evaluated using an experimental model of ischemia-reperfusion of randomized skin flaps on the back of rats. Fifty-four young Wistar rats, average weight 267,2 g, were distributed randomly in three groups (GC-saline control, AK-kaurenoic acid group, GA – L-arginine group), numerically equal and subsequently redistributed into three subgroups (T-0, T-1 and T-2) with six animals each. All surgical procedures were performed under general anesthesia, using a combination of ketamine hydrochloride (90 mgkg) with xylazine (10mgkg), administered intraperitoneally.(ip). Groups GC and KA rats received the drugs used in this study by gavage; GA rats received LA ip. Treatments were provided 2: hours before the experiment (T0) and 24h (T1). T3 rats (168 h) received daily (6) doses of KA, until sacrifice. Skin concentrations of IL-1 β, TNF-α, MDA, GSH, MPO, Nitrite/Nitrate (Nox) ratio and MPO activity ere assayed.. The Kolmorogov-Smirnov test was used for determination of the distribution pattern of the samples. The data are presented as mean ± SE. ANOVA followed by the Dunnett test, were used for statistical evaluation. Values of p 0.05 were considered statistically significant KA promoted a significant reduction of IL-1, TNFα and MDA concentrations, after 24/48 h of randomized cutaneous flap construction demonstrating anti-inflammatory and antiperoxdative activities. LA promoted significant decrease of MDA concentration at T1 timepoint, and a significant increase in GSH concentration in 24/48 h timespoints, demonstrating its antiperoxidative and antioxidant activities. KA also promoted a sigbnificant increase in GSH concentrations after 24/48h. KA promoted significant decrease of MPO activity after 24h48h, showing anti-inflammatory activity. KA and LA promoted a significant decrease of the nitrite/nitrate ratio at T1, showing antioxidant activity. However, at 168 h timepoint the use of LA promoted significant increase of nitrite/nitrate ratio, demonstration a pro-oxidant activity. It is concluded that KA presents antiperoxidative action and intense antioxidant and anti-inflammatory activity while LA presents antiperoxidative and antioxidant action, during ischemia and reperfusion of randomized cutaneous flap rats